The vital two: Retail innovation by Sol Price and Sam Walton - Art Carden; Charles Courtemanche; Reginald Harris (Essays in Economic & Business History (EEBH), 2022)
Sol Price and Sam Walton changed retail in the twentieth century. Price changed retail by combining knowledge he assembled from real estate law and the firms he observed to find creative ways to innovate in discount retail. Walton, too combined and redeployed knowledge-in some cases, the knowledge he obtained watching Price. Walton also used the knowledge he acquired from studying retail logistics to develop a supply chain that dramatically lowered costs and passed those savings onto consumers. Both succeeded by developing organizations that effectively deployed entrepreneurial judgment. Their careers provide informative examples of the judgment-based approach to entrepreneurship.
Keywords: N82; L26; 330; Walmart; retail; Sam Walton; Sol Price; judgment-based approach; entrepreneurship; effectuation